Improving measurement technology for the design of sustainable cities. (16th August 2017) - Pardyjak, Eric R; Stoll, Rob
Abstract: This review identifies and discusses measurement technology gaps that are currently preventing major science leaps from being realized in the study of urban environmental transport processes. These scientific advances are necessary to better understand the links between atmospheric transport processes in the urban environment, human activities, and potential management strategies. We propose that with various improved and targeted measurements, it will be possible to provide technically sound guidance to policy and decision makers for the design of sustainable cities. This review focuses on full-scale in situ and remotely sensed measurements of atmospheric winds, temperature, and humidity in cities and links measurements to current modeling and simulation needs. A key conclusion of this review is that there is a need for urban-specific measurement techniques including measurements of highly-resolved three-dimensional fields at sampling frequencies high enough to capture small-scale turbulence processes yet also capable of covering spatial extents large enough to simultaneously capture key features of urban heterogeneity and boundary layer processes while also supporting the validation of current and emerging modeling capabilities.